2020
DOI: 10.1007/s00265-020-02927-9
|View full text |Cite
|
Sign up to set email alerts
|

When night never falls: female sexual signalling in a nocturnal insect along a latitudinal gradient

Abstract: The environment can play an important role in animal communication by affecting signal transmission and detection. Variation in the signalling environment is expected to be especially pronounced in widely distributed species, potentially affecting how their signals are detected. Such environmental variability is presumably relevant for sedentary females of a nocturnal capital breeder, the European common glow-worm (Lampyris noctiluca), which produce green light during the night to attract flying males to mate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…These results could be explained by larger females being brighter (Hopkins et al 2015) and hence having a higher probability to attract males under artificial light than smaller females (Elgert et al 2021). Conversely, small females may be able to attract mates only during the darkest hours of the night (Borshagovski et al 2020). Given that small females start their glow later, and cease it more easily under light, artificial light shortens the time available for mate attraction relatively more in small than large females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results could be explained by larger females being brighter (Hopkins et al 2015) and hence having a higher probability to attract males under artificial light than smaller females (Elgert et al 2021). Conversely, small females may be able to attract mates only during the darkest hours of the night (Borshagovski et al 2020). Given that small females start their glow later, and cease it more easily under light, artificial light shortens the time available for mate attraction relatively more in small than large females.…”
Section: Discussionmentioning
confidence: 99%
“…Given that small females start their glow later, and cease it more easily under light, artificial light shortens the time available for mate attraction relatively more in small than large females. Similarly, the effects of artificial light on the glow and its initiation may differ across latitudes (Dreisig 1978), with females presumably needing a larger size and brighter glow to attain an adequate visibility in higher latitudes (Borshagovski et al 2020), providing an interesting topic for further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from buildings belonging to the research station at the end of the road, there is a low number (< 10) of houses along the road, and only a short stretch of it has streetlights (~100 m, on one side). The study site was selected due to the logistic convenience of it being close to the research station and because previous studies had showed that glow-worms inhabit the area (Borshagovski et al 2019(Borshagovski et al , 2020Elgert et al 2020Elgert et al , 2021Lehtonen and Kaitala 2020). More generally, the European glow-worm has a wide range from Iran (N32°) to central Finland (N64°) (Samin et al 2018;Borshagovski et al 2020), with the species being on the decline across Europe, as are many other Lampyrid species globally (Lewis et al 2020).…”
Section: Methodsmentioning
confidence: 99%